The Historical Narrative for Indonesia as A Multiethnic State: A Methodological Exploration - Purwanta, Hieronymus (Paramita: Historical Studies Journal, 2022)
This study aims to analyze Indonesian historiography for education from a methodological perspective. The main problem raised was what historical narratives are suitable for the Indonesia as a multiethnic state? This research analyzes the historiography for education published along the New Order period (1967-1998) to the Reformation era (1998-now). The approach used was hermeneutic developed by Heidegger and Gadamer. They view that an audience is a crucial person in interpreting historical narrative. The historiographical study results indicate that the historical narrative developed did not represent objective, deterministic, and monolithic. This study not only criticized the Indonesian history narrative that was published but also offered the use of Inter-Ethnics Relations and 'History from within' approach as the solution. The inter-Ethnics Relations approach highlights the intensity of positive interactions between ethnics to eliminate prejudice and conflict. On the other hand, history from within approach makes historical events understood as representations of the socio-cultural system. Historical action is interpreted and understood as an effort to realize the ideal life order under historical actors' values and culture. Through these two approaches, the historical narrative makes sense for people from all ethnicities as citizens of the Indonesia.Penelitian ini bertujuan untuk menganalisis historiografi Indonesia untuk pendidikan dari perspektif metodologis. Masalah utama yang diangkat adalah narasi sejarah apa yang cocok untuk Indonesia sebagai negara multietnis? Penelitian ini menganalisis historiografi pendidikan yang diterbitkan pada masa Orde Baru (1967-1998) hingga era Reformasi (1998-sekarang). Pendekatan yang digunakan adalah hermeneutik yang dikembangkan oleh Heidegger dan Gadamer. Mereka memandang bahwa penonton adalah orang yang sangat penting dalam menafsirkan narasi sejarah. Hasil kajian historiografis menunjukkan bahwa narasi sejarah yang dikembangkan tidak merepresentasikan objektif, deterministik, dan monolitik. Kajian ini tidak hanya mengkritisi narasi sejarah Indonesia yang diterbitkan tetapi juga menawarkan penggunaan Hubungan Antar Etnis dan pendekatan 'Sejarah dari dalam' sebagai solusinya. Pendekatan Hubungan Antar Etnis menyoroti intensitas interaksi positif antar etnis untuk menghilangkan prasangka dan konflik. Di sisi lain, pendekatan sejarah dari dalam membuat peristiwa sejarah dipahami sebagai representasi dari sistem sosial budaya. Tindakan sejarah dimaknai dan dipahami sebagai upaya mewujudkan tatanan kehidupan yang ideal di bawah nilai dan budaya pelaku sejarah. Melalui dua pendekatan ini, narasi sejarah masuk akal bagi orang-orang dari semua etnis sebagai warga negara Indonesia.Cite this article: Purwanta, H. (2022). The Historical Narrative for Indonesia as A Multiethnic State: A Methodological Exploration. Paramita: Historical Studies Journal, 32(1), 117-126. http://dx.doi.org/10.15294/paramita.v32i1.31124